Physico-chemical features of water in Betana wetland, Belbari, Morang, Nepal - Thapa, Ganesh Bahadur; Pal, Joydeb (Himalayan Journal of Science and Technology, 2018)
Different physico-chemical parameters in Betana wetland pond water was studied for two years. Air temperature showed positive and significant correlation with water temperature (r =0.947, P